Isolation and Characterization of Human Monoclonal Antibodies That Recognize the Influenza A(H1N1)pdm09 Virus Hemagglutinin Receptor-Binding Site and Rarely Yield Escape Mutant Viruses - Yasuhara, Atsuhiro; Yamayoshi, Seiya; Ito, Mutsumi; Kiso, Maki; Yamada, Shinya; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2018)
The influenza A virus rapidly mutates to escape from antibodies. Here, we isolated and characterized three human monoclonal antibodies (mAbs) that neutralize A(H1N1)pdm09 viruses. Generation of escape mutant viruses suggested that these antibodies recognized conserved residues of the receptor-binding site (RBS) of hemagglutinin (HA) and that mutant viruses that escaped from these mAbs rarely appeared. Moreover, the escape mutant viruses grew significantly slower than wild-type virus, indicating their reduced fitness. These results indicate that these three human mAbs against the RBS of HA have the potential to be anti-influenza agents with a low propensity for the development of resistant viruses.